The Effect of Third Party Funds, CFO, Debt Ratio on Earning Quality of Islamic Commercial Bank - Tusa'dya, Halima; Rahma Wijayanti (Airlangga Journal of Innovation Management, 2024)
This study aims to analyze the factors that affect Earnings Quality. This research will offer a new and broader view on the factors that influence the profit quality of Islamic commercial banks in Indonesia. This research use quantitative study that uses multiple regression analysis methods. The data used is panel data from 2019-2022. The factors analyzed for their influence in this study are Third Party Funds, CFO, and DER. The model estimation used is multiple regression analysis with a quantitative descriptive method. The results of the study show that the CFO and DER have an impact on earnings quality, while, third third-party Funds do not affect Earnings Quality. These findings indicates that banks need to pay more attention to managing operating cash flow (CFO) and capital structure (DER) to improve earnings quality. Proper management of these two variables can help banks achieve more stable and transparent financial performance. Although Third Party Funds do not significantly affect earnings quality, their management is still important to maintain the stability of the bank’s liquidity. These results also suggest that investors and other stakeholders may need to focus on CFO and DER as key indicators when assessing a bank’s earnings quality.